Maximizing the Civil Mission of Universities - Hazelkorn, Ellen (International Higher Education, 2019)
The contribution and impact of universities on the cities and regions in which they are based is an increasing focus of government policy. This builds upon their public good role with respect to knowledge creation and dissemination, but it also responds to problems of deep social and economic inequality in our societies. Wales is no different. In the belief that universities can make a significant contribution, the Welsh government commissioned a report seeking to maximize Welsh universities civic mission.